Parental burnout during COVID-19 pandemic among nurses - Valasavičienė, Deimantė; Razbadauskas, Artūras; Skarbalienė, Aelita (Slauga. Mokslas ir praktika, 2021)
Parenting is a complex and stressful activity. Prolonged extreme parental stress can lead to parental burnout. Parental burnout develops when parental resources (emotional, cognitive, psychological, financial, etc.) are insufficient to meet current and emerging needs. The COVID-19 pandemic has caused great stress and anxiety to many parents around the world. For healthcare professionals, the pandemic period is particularly difficult due to increased stress in the workplace. Constant stress in the workplace and at home can lead to severe psychological illnesses. The aim of this study was to reveal the parental burnout of nurses during COVID-19. A quantitative study was conducted using the Parental Burnout Assess-ment tool. The participants were nurses (n = 200) raising pre-school and school age children. The results revealed that nurses experienced relatively mild burnout in parenting activities, presumably due to the possibility to work in the workplace (not from home) without juxtaposing work and children’s learning problems. Greater burnout is caused by younger age of parents, higher education, higher number of children living together, and time spent helping children with education. Persons who have used the services of babysitters or children’s centres/clubs before the national lockdown experi-ence more severe burnout in parenting activities.